2016
DOI: 10.1097/mcg.0000000000000473
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Clostridium difficile Health-related Quality-of-Life Questionnaire

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 34 publications
1
69
1
Order By: Relevance
“…In that particular study, the direct treatment costs of CDI recurrence were estimated at €73,898 per patient with one or more recurrence [ 69 ]; this is four times greater than the incremental cost estimates for recurrent CDI reported in the US-based systematic review mentioned above [ 13 ]. It has also been shown that recurrent CDI has a greater impact on patients’ quality of life than the initial episode [ 70 ]. Taken together, these data suggest that fidaxomicin may be more cost-effective than suggested by the results of our systematic literature review of EEs.…”
Section: Discussionmentioning
confidence: 99%
“…In that particular study, the direct treatment costs of CDI recurrence were estimated at €73,898 per patient with one or more recurrence [ 69 ]; this is four times greater than the incremental cost estimates for recurrent CDI reported in the US-based systematic review mentioned above [ 13 ]. It has also been shown that recurrent CDI has a greater impact on patients’ quality of life than the initial episode [ 70 ]. Taken together, these data suggest that fidaxomicin may be more cost-effective than suggested by the results of our systematic literature review of EEs.…”
Section: Discussionmentioning
confidence: 99%
“…The only other disease-specific PRO questionnaire developed for this patient population is the Cdiff32, a 32-item instrument that has recently been reported to measure HRQOL in patients with CDI [31]. Unlike the CDI-DaySyms, the Cdiff32 is not a CDIsymptom-specific daily diary but rather a measure of the bother and/or impact of CDI on patients' daily activities, anxiety, diet, sleep, discomfort, health perception, dysphoria, relationships, and social interactions, with a recall period of the past 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the two instruments were developed differently. Although the symptoms included in the CDI-DaySyms were elicited from patients with CDI until saturation was reached, the items in the Cdiff32 were identified through a literature research, and although clinicians and patients assessed the relevance of these items, no attempts were apparently made to elicit additional HRQOL items from patients or to document via a saturation grid that all relevant concepts were included [31]. The present qualitative research study to develop the CDI-DaySyms had several strengths.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, Wilcox et al used the EQ-5D-3 L questionnaire and the EQ visual analogue scale to explore HRQoL changes in CDI participants [23] and Garey et al developed a health-related quality of life instrument (Cdiff32) based on the RAND Short-Form 36 (SF-36). Garey et al demonstrated that there was no consensus towards assessment of CDI participants' quality of life [20]. Therefore, our survey did not include these previously considered questionnaires.…”
Section: Survey Questions (See Electronic Supplementary Materials A1)mentioning
confidence: 99%
“…Despite a scarcity of quality of life data in those with CDI, chronic diarrhea in patients with HIV or those having received a kidney transplant has shown significant reductions in health-related quality of life, including decreased general well-being, social, and physical functioning [18,19]. Only one study by Garey et al [20] has attempted to develop and validate a questionnaire of quality of life taking into account the specificities of CDI. To date, the specific impact of CDI on patient-reported Health-Related Quality of Life (HRQoL) has not been thoroughly studied [19,21,22].…”
Section: Introductionmentioning
confidence: 99%